The Penguin Lessons: A True Story - Michell, Tom
A unique and moving real-life story of the extraordinary bond between a young teacher and a penguin, this book will delight readers who loved Marley & Me, Dewey the Library Cat, The Good Good Pig, and any book by Jon Katz. In 1975, twenty-three-year-old Englishman Tom Michell follows his wanderlust to Argentina, where he becomes assistant master at a prestigious boarding school. But Michell's adventures really begin when, on a weekend in Uraguay, he rescues a penguin covered in oil from an ocean spill, cleans the bird up, and attempts to return him to the sea. But the penguin refuses to leave his rescuer's side. "That was the moment at which he became my penguin, and whatever the future held, we'd face it together," says Michell in this charming memoir. Michell names the penguin Juan Salvador ("John Saved"), but Juan Salvador, as it turns out, is the one who saves Michell. After Michell smuggles the bird back to Argentina and into his campus apartment, word spreads about the young Englishman's unusual roommate. Juan Salvador is suddenly the center of attention--as mascot of the rugby team, confidant to the dorm housekeeper, co-host of Michell's parties, and an unprecedented swimming coach to a shy boy. Even through the collapse of the Peronist government and amid the country's economic and political strife, Juan Salvador brings joy to everyone around him--especially Michell, who considers the affectionate animal a compadre and kindred spirit. Witty and heartwarming, The Penguin Lessons is a classic in the making, a story that is both absurd and wonderful, exactly like Juan Salvador"-- "Whether as rugby team mascot or assistant swimming coach, the penguin known as Juan Salvador touches and transforms everyone he encounters, including Tom Michell, the young teacher who finds him and rescues him from an oil spill disaster. After a time, Juan Salvador (meaning "the saved one") receives a new name: Juan Salvado, or "the savior." Set against the turbulent world of political unrest of 1970s Argentina, this multi-layered true story is a testament and tribute to animals and will no doubt resonate with the people who love them